Farmers of the world, unite! - Melo, Ivaro Soares de (Technical Centre for Agricultural and Rural Cooperation, 2003)
Farmers have improved agriculture by breeding plants and animals and building sustainable systems of production. They have borne the brunt of agricultural and industrial revolutions too. Yet forces outside agriculture dictate its production and...